The role of gastric aspirates cytology and micro-erythrocyte sedimentation rate in predicting the early septicemia in newborn babies - Yadav, Meetu; Gupta, Raksha; Singh, Jasbir; Saraswath, Sameer; Nagaraj, Niranjan; Bana, Sailen Kumar (Indian Journal of Child Health, 2018)
Background: Sepsis is an important cause of neonatal morbidity and mortality. The magnitude of problem may be reduced by early detection of amniotic fluid infections and appropriate treatment of the neonate. Objective: The objective of this study was to know the role of gastric aspirates cytology and micro-erythrocyte sedimentation rate (m-ESR) in predicting the early-onset septicemia in newborn babies. Materials and Methods: The study was conducted on 100 neonates with suspected septicemia and 50 normal neonates admitted to neonatology section of a tertiary care hospital. Blood sample and gastric aspirate sample were collected for sepsis screening of the neonates. All the collected data were tabulated and statistically analyzed using SPSS 2.0 software. Results: About 55% of neonates had positive cytology and m-ESR and 22.2% had subsequent sepsis. Combined sensitivity was 50%, specificity was 81.25%, positive predictive value (PPV) was 62.5%, and negative predictive value (NPV) was 72.2%. Of the 45% of cases with positive cytology and micro-ESR, 13.3% had septicemia, 6.6% had pneumonia, and 2.2% had meningitis. The other 55% of cases had negative cytology and m-ESR, and out of them, 9.09% had septicemia, 7.2% had pneumonia, and 1.8% had meningitis. The sensitivity of m-ESR was 60%, specificity was 62.5%, PPV was 50%, and NPV was 71.5%. The combined sensitivity was 50%, specificity was 81.25%, PPV was 62.5%, and NPV was 72.2%. Conclusion: Combined gastric aspirate and m-ESR had high percentage of specificity and NPV. No specific and significant correlation between positive gastric aspirate cytology and rural/urban area, birth weight, sex, gestation, prolong labor, meconium-stained amniotic fluid, and mode of delivery was found.